Biologically inspired robotics - Liu, Yunhui; Sun, Dong, 1967- (Boca Raton, Fla. : CRC Press, 2012)
"Based on a selection of presentations from the 2009 IEEE International Conference on Robotics and Biomimetics, this reference presents cutting-edge research in the field. The 16 chapters, rewritten to include extra detail and analysis, cover robotic design, micro/nano robots for bio-systems and biomedicine, and biological measurement and actuation. A section on cybernetics is also included. Written for graduate students and researchers in control engineering and robotics, this text helps readers understand research trends, future development of bio-robotics, and biologically inspired robot design. It includes a wealth of figures and hundreds of equations"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Robotics; Bionics; Biomimicry; Biomechanics; Electronic books